Influence of contact behavior on welding distortion and residual stress in a thin-plate butt-welded joint performed by partial-length welding. (July 2022) - Li, Xixian; Hu, Long; Deng, Dean
Abstract: Partial-length butt-welded joint is a typical weldment which is often used in vehicle parts such as car door and body. In order to clarify the influence of contact behavior on the final distortion and residual stress distribution in thin-plate butt-welded joints, a computational approach considering multiple nonlinearities was proposed based on ABAQUS code, and a series of three-dimensional thermal–elastic–plastic finite element models were developed to simulate welding distortion and residual stress in mild steel thin-plate butt-welded joints performed by partial-length welding. Meanwhile, the corresponding experiments were carried out to verify the calculation accuracy of the proposed computational approach. Moreover, the influence of initial gap size on welding distortion and residual stress was numerically and experimentally examined. Based on the simulated results, the formation mechanism of welding deformation in the thin-plate partial-length butt-welded joint was also discussed. Highlights: An advanced computational approach was developed to simulate residual stress and distortion for thin-plate joints. The influence of contact behavior on welding distortion and residual stress of a butt-welded joint was clarified. The formation mechanism of deflection in partial-length butt-welded joint was clarified. The influence of initial gap size on welding distortion and residual stress was clarified.